KAJI EKSPERIMENTAL KOEFISIEN KERUGIAN PADA PERCABANGAN PIPA DENGAN SUDUT 450, 600 DAN 900 - Muchsin, Muchsin; Subagyo, Rachmat (Jurnal MEKANIKAL, 2011)
During fluid flow through the system piping installation happened many so-called pressure loss as the major pressure loss and minor pressure loss (loss due to fluid passing through a branching). Distribution of the fluid flow in branching is an irreversible process. This irreversibelitas in the application techniques will reduce the performance of a system. Attemps to find out how big the losses incurred by branching pipe is to measure the coefficient of losses incurred. The form of experiments performed was to make three pieces of pipe brnching angles galvanic type medium with 450, 600 and 900. Re variation of 0 to 5,5 x 104. The results showed that the coefficient Of loss for k3-2 branch (45)= k3-2 (60)= K3-2 (90)= (0,07 to 0,39) and k3-1 branch (45)= (0,95- 0,60), K3-1 (60)= (1,08 to 0,85), K3-1 (90)= (1,10- 1,50), for a total coefficint Ktot (45)= (1,02 to 0,97), Ktot (60)= (1,15 to 1,23), Ktot (90)= (1,17 to 1,89).